Effect of phototherapy on hematological profile of newborns with unconjugated hyperbilirubinemia - Timilsina, Mukunda; Gauchan, Eva; BK, Ganesh (Journal of Chitwan Medical College, 2021)
Background: Phototherapy despite being very safe is found to be associated with various untoward effects. The objective of this article was to study the changes in various hematological parameters as a result of phototherapy in neonates treated for unconjugated hyperbilirubinemia. Methods: A cross sectional study was conducted in 120 neonates with unconjugated hyperbilirubinemia to determine the changes in the blood cell counts. We compared the complete blood counts at the time of admission and after 48 hours of phototherapy. The data was analyzed in SPSS 25 using paired t test. Results: We observed that there was an increase in the lymphocyte counts from 5,650 cells/mm3 before phototherapy to 6,360 cells/mm3 after phototherapy with a p-value 0.028. MCH increased from 32.22 pg before phototherapy to 33.34 pg after phototherapy with a p-value of 0.018. The mean monocyte counts decreased from 730 cells/mm3 before phototherapy to 530 cells/mm3 after phototherapy with a p-value of 0.016. The mean platelet count also decreased from 241×103 cells/mm3 to 258×103 cells/mm3 with a p-value of 0.041 which was significant. Rest of the blood cell counts seem to be unaltered by phototherapy. Conclusions: Phototherapy was found to be associated with significant decrease in the absolute monocyte count and platelet counts and caused an increase in the lymphocyte count and MCH. However, it does not cause significant changes in the total count and hemoglobin levels.